2019
DOI: 10.1097/nmd.0000000000001021
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Weight-Related Self-Stigma and Mental Health for Overweight/Obese Children in Hong Kong

Abstract: This study aimed to test the differences of weight-related self-stigma and mental health conditions between overweight (OW) and non-OW children in Hong Kong. The correlations between weight-related self-stigma and mental health conditions were also investigated. Children aged 8 to 12 years (n = 367; 198 boys) completed questionnaires on weight-related self-stigma (Weight Bias Internalization Scale [WBIS] and Weight Self-Stigma Questionnaire [WSSQ]) and mental health conditions (Brief Symptom Rating Scale-5 [BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 36 publications
1
39
0
2
Order By: Relevance
“…Research among adults suggests that sociodemographic variables, such as socioeconomic status, gender and age, might also contribute to WBI [23,24]. With regard to children, no effects of age on WBI were observed across different age groups [15][16][17][18][19]. Concerning gender, previous evidence is inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research among adults suggests that sociodemographic variables, such as socioeconomic status, gender and age, might also contribute to WBI [23,24]. With regard to children, no effects of age on WBI were observed across different age groups [15][16][17][18][19]. Concerning gender, previous evidence is inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Ratcliffe and Ellison [14] have addressed several variables that might enhance vulnerability to WBI. Obviously, higher weight status and experienced weight stigmatization are detrimental factors for WBI in children and adolescents [11,[15][16][17][18]. Beyond that, the authors [14] postulate that body dissatisfaction, self-esteem and emotional problems are not only consequences of, but also predisposing factors for WBI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that weight‐related self‐stigma indirectly predicts binge eating via food addiction. It is not surprising that food addiction was the strongest mediator between weight‐related self‐stigma and binge eating because individuals with obesity have higher weight‐related self‐stigma (Chan et al, ). It has also been reported that individuals with food addiction are typically overweight or obese (Barry, Brescoll, Brownell, & Schlesinger, ; Gearhardt et al, ; Gearhardt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Internalized stigma is defined as the acceptance of stigma by a stigmatized person as part of the person's own system of values and self-concept [12]. Studies on the groups with high levels of stigma, such as people with mental illness [13][14][15][16][17][18][19][20] or family members of people with mental illness [21][22][23][24][25][26], children with learning disabilities [27], people with epilepsy [28], people with weight concerns [29][30][31][32][33][34][35][36][37][38][39], and people with HIV [40][41][42] highlight the highly negative effects of internalized stigma. However, so far, research on the internalized stigma of people with disability and its consequences is scarce.…”
Section: Introductionmentioning
confidence: 99%